Diogo Bernardes's brandura - Park, S (Duke University Press, 2017)
Readers of Diogo Bernardes’s (c.1530-c. 1595) poetry have long praised the brandura (gentleness) of his work. But what brandura meant and how positively this quality was viewed shifted depending on the context of discussion. Brandura was associated with the middle style, mastery of elocutio, and, by extension, with poetry’s ability to move those who listened to or read it. Because of this, brandura could, at one moment, provoke moral anxiety, and at another, could signal the height of poetic accomplishment. In quarrels over the relative merits of the different European vernaculars, apologists of the Portuguese language invested in Bernardes’s reputation as brando (gentle) as he was said to demonstrate the brandura of their mother tongue. Yet, later in the seventeenth century, Bernardes’s fortunes sank. Though Bernardes is currently little esteemed, his association with the multiple meanings of brando and brandura implicated him in a series of important political, moral, and aesthetic disputes throughout the sixteenth and seventeenth centuries. Through renewed attention to style and affect in the context of cultural history, the present essay aims to revive interest in his work in the present.